Countryside, Domestic Picturesque, and Scenic Sublimes: The Triad of Eco-feminism in Sarah Orne Jewett’s “A White Heron” - Sasa, Ghada; NimerAbdalqader Abu Jweid, Abdalhadi (Dirasat: Human and Social Sciences, 2022)
This paper examines countryside, domestic picturesque, and scenic sublimes in Sarah Orne Jewett’s “A White Heron.” It conducts an interdisciplinary eco-feminist approach to explore the coalescence of women and nature depicted in the story. The study approaches women’s exploitation and its remedial antithesis through living in nature. It applies three eco-critical concepts. The first concept is the countryside which comprises marshes, swamps, and woods. The second concept is domestic picturesque that encompass fauna and paths; and the third concept is scenic sublimes including birds, forest, and wilderness. The study demonstrates how Jewett adopts these eco-critical insights as indicatory features symbolizing the exploitation of women by male mainstream to dramatize the subtle relation between women and nature. It highlights an aspect seldom remarked on by scholars of Jewett’s story, and it discovers Jewett’s self-conscious exposition of women’s exploitation inflicted on the protagonist, Sylvia. It also identifies Jewett’s depiction of the protagonist’s settlement in the countryside to evade masculine exploitation by living close to natural elements, like animals, birds, and wilderness. The study ultimately unravels Jewett’s reinforcement of the protagonist’s feminist subjectivity via finding spiritual serenity in nature.